WEBSITE PENGARSIPAN MNC SEKURITAS (STUDY KASUS MNC SEKURITAS JAMBI): System;Information;DFD;Website. - Wati, Nila; Riswan; Yeniwati, Desy (JURNAL AKADEMIKA, 2021)
Information systems have a very important role in the development of an agency, especially at PT. MNC Securities Jambi. PT. MNC Sekuritas Jambi which apparently has not optimized the development of the information system. This causes the processing of archiving data PT. MNC Sekuritas Jambi became ineffective and inefficient. This study aims to analyze and study the problems in data processing archiving PT. MNC Sekuritas Jambi, a web-based information system that can make it easier for admins to process archiving data. The method used in this study is the Waterfall method and is supported by a systems analysis approach that uses object-oriented methods with data flow diagrams or data flow diagrams (DFD). This research resulted in data processing of incoming and outgoing mail archiving at PT. MNC Sekuritas Jambi is web-based which can make it easier for admins to manage data.